Canine Pluripotent Stem Cells: Are They Ready for Clinical Applications? - Betts, Dean H.; Tobias, Ian C. (Frontiers in Veterinary Science, 2015)
The derivation of canine embryonic stem cells and generation of canine induced pluripotent stem cells are significant achievements that have unlocked the potential for developing novel cell-based disease models, drug discovery platforms and transplantation therapies in the dog. A progression from concept to cure in this clinically relevant companion animal will not only help our canine patients but also help advance human regenerative medicine. Nevertheless, many issues remain to be resolved before pluripotent cells can be used clinically in a safe and reproducible manner.